Microstructure and mechanical property of high power laser powder bed fusion AlSi10Mg alloy before and after T6 heat treatment. Issue 4 (2nd October 2022) - Liu, Mengna; Wei, Kaiwen; Zhou, Runsen; Yue, Xiaoze; Zeng, Xiaoyan
ABSTRACT : This paper focuses on the microstructure and mechanical property of the high power laser powder bed fusion AlSi10Mg alloy before and after T6 heat treatment. The results demonstrate that the as-printed sample presents a columnar grain structure along the build direction and a strong <100> texture. Inside the columnar α-Al grains, there are cellular dendrites decorated with network eutectic Si. Both the α-Al matrix and eutectic Si have high-density dislocations. Besides, nano-twins and stacking faults are observed in eutectic Si. After T6 treatment, although the α-Al matrix still exhibits a columnar solidification feature, the cellular dendrites disappear and the proportion of equiaxed grains increase. And the eutectic Si presents as separate plates or nanoscale particles, in which nano-twins and stacking faults are not found. The tensile property anisotropy decreases and the strength-ductility balance improves after T6 treatment. The evolution mechanisms of the microstructure and tensile property are revealed. GRAPHICAL ABSTRACT: UF0001